Risk Management and School Effectiveness under the Secondary Educational Service Area Office 9 - Sangnuan, Porrung (Arts of Management Journal, 2020)
The purposes of this study were: 1) to determine the risk management under the Secondary Educational Service Area Office 9; 2) to determine the effectiveness of the school under the Secondary Educational Service Area Office 9; and 3) to determine the relationship between the risk management and school effectiveness under the Secondary Educational Service Area office 9. By specifying samples from the approximate size table of Krecie and Morgan. The sample size of this study was 56 schools. The respondents from each school were; a school director and a teacher who responsible for internal quality assurance, with a total of 112 respondents. The instrument for collecting the data were an opinionnaire. The statistical treatments were frequency, percentage, arithmetic mean, standard deviation, and Pearson’s product moment correlation coefficient. The findings of this study were as follows: 1) The risk management under the Secondary Educational Service Area Office 9 as a whole and each aspect were at the highest level; 2) The effectiveness of the school under the Secondary Educational Service Area Office 9 as a whole and each aspect were at the highest level; and 3) There were significant relationship between the risk management and the effectiveness of the school under the Secondary Educational Service Area Office 9 as a whole and each aspect with a statistically significant 0.01 level.